Lactobacillus acidophilus extracellular vesicles-coated UiO-66-NH2@siRNA nanoparticles for ulcerative colitis targeted gene therapy and gut microbiota modulation - Chenyang Cui; Jiaze Tang; Jie Chen; Beining Zhang; Ruonan Li; Qiang Zhang; Chunjing Qiu; Rongchen Chen; Geng Min; Zhaowei Sun; Haibo Weng (Journal of Nanobiotechnology)
Abstract Ulcerative colitis (UC) is a complex and chronic inflammatory bowel disease whose pathogenesis involves genetic and environmental factors, which poses a challenge for treatment. Here, we have designed an innovative integrated therapeutic strategy using Lactobacillus acidophilus extracellular vesicles (EVs) to encapsulate UiO-66-NH2 nanoparticles bounded with TNF-α siRNA (EVs@UiO-66-NH2@siRNA) for UC treatment. This system shows superior affinity to inflammation-related cells due to the Lactobacillus acidophilus EVs can maintain immune homeostasis by regulating the secretion of cytokines in vitro. siRNA can specifically target the key inflammatory TNF-α in UC and silence its gene expression, thereby regulating the process of inflammatory response. After oral administration, EVs@UiO-66-NH2@siRNA demonstrates an accurate delivery of TNF-α siRNA to colonize the colon site and exerts a siRNA therapeutic effect by inhibiting the expression of TNF-α, which alleviates the intestinal inflammation in DSS-induced UC model. Moreover, this system can modulate the types and compositional structures of gut microbiota and metabolites to achieve an anti-inflammatory phenotype, which is helpful for the repair of intestinal homeostasis. We also have proved that UiO-66-NH2 nanoparticles exhibit a high loading capacity for TNF-α siRNA and good pH responsiveness, improving the potent release of siRNA in colon tissue. Collectively, the EVs@UiO-66-NH2@siRNA nano-delivery system demonstrate a feasible combination therapeutic strategy for UC through gut microecology modulation, immune regulation and TNF-α siRNA silence, which may provide a potential targeted treatment approach for inflammatory bowel disease. Graphical Abstract